Spatial distribution, risk and potential sources of lead in soils in the vicinity of a historic industrial site - Qu, Changsheng; Wang, Shui; Ding, Liang; Zhang, Mancheng; Wang, Dong; Giesy, John P. (Chemosphere (Oxford), 2018)
Because of measures taken by local and national government agencies to control releases of metals, former industrial sites in China that are contaminated with lead (Pb) in soils have been abandoned. Compared with historic sites themselves, little attention has been paid to contamination with Pb in areas surrounding these sites. In this study, a method by integrating sequential extraction and isotopic fingerprinting was proposed to reveal the key fractions of Pb contaminants in soils, trace their sources and determine the subject of liability for remediation. Topsoils from near a historic site, where lead oxide was produced, were found to be contaminated. Concentrations of Pb in soils were inversely proportional to distances from the industrial site and depth in soils. The predominant form of Pb was the Fe/Mn-oxide-bound fraction (FM3), which accounted for from 53.39% to 82.07% of total concentrations of Pb. Concentrations of Pb in vegetables produced on contaminated soils exceeded those allowed in food for consumption by humans. An assessment of hazards and risks posed by consumption of vegetables grown on these soils indicated relatively high potential for adverse effects on local residents around the closed plant. By use of isotopic finger printing for Pb, the abandoned factory was determined to be the most likely source of Pb in topsoils, especially fraction FM3. To mitigate exposures of people to Pb via consumption of locally produced food, recommended strategies should target legacy sources of Pb to soils in the vicinity of this historic industrial site. [Display omitted] •Surface soils near a site where historically, lead oxide was produced, were contaminated with Pb.•Results of sequential extractions showed that predominant form of Pb was that bounds to Fe/Mn-oxides.•Predicted, daily intake of Pb by local inhabitants, via consuming homegrown vegetables, exceeded benchmark doses.•The isotopic patterns of Pb in soil and vegetables resembled that of lead oxide previously processed at the industrial site.•Source tracing will have critical implications for future measures to reduce risks posed by Pb.